MANUNGGALING KAWULO GUSTI ‎MENURUT ALIRAN SAPTA DARMA ‎DITINJAU DARI AGAMA ISLAM - Purwandari, Rika (Jurnal Ushuluddin, 2022)
The purpose of this research is, first, to understand the meaning of Manunggaling Kawulo Gusti and, second, to examine the Islamic perspective on Manunggaling Kawulo Gusti and the Sapta Darma movement. The results of this study show that Manunggaling Kawulo Gusti refers to the unity of humans with their God. From the perspective of Islam, Manunggaling Kawulo Gusti in the Sapta Darma movement is considered misguided. In terms of worship practices, Sapta Darma essentially shares similarities with Islam, as both worship Allah, the Almighty. However, the methods of worship differ. In Sapta Darma, the daily worship practices of its followers are different from those in Islamic Sharia. For example, Sapta Darma adherents do not perform the five daily prayers as required in Islam but only pray once a day, and even then, the way they perform their prayers does not follow the Islamic pillars of prayer. Manunggaling Kawulo Gusti in the Sapta Darma movement is considered a belief system in line with Sapta Darma teachings, as the practice of worship in Sapta Darma is seen as one manifestation of the Manunggaling Kawulo Gusti concept.